Studi Deskriptif Brunout pada Guru yang Melaksanakan Pembelajaran Jarak Jauh - Adnan Bintang; Sita Rositawati (UNISBA Press, 2022)
Abstract. Since the Covid-19 pandemic, the learning process has been carried out using a distance learning system. According to several survey results on teachers who teach with a distance learning system, it shows the occurrence of burnout symptoms in teachers who do distance learning. Burnout is a syndrome of emotional exhaustion, depersonalization, and a decreased sense of achievement and personal accomplishment. This study aims to get an overview of burnout for teachers who carry out distance learning in the city of Bandung, the measurements are carried out using the MBI-ES (Maslach Burnou Inventory-Education Survey) measuring instrument which has been adapted by Aulia Hanifah (2019) Sample: 266 Teachers who do PJJ in Bandung City. Based on the results of the study showed that 82% of subjects experienced high burnout, with the highest aspect being low personal accomplishment, this study showed that a number of 216 respondents (82%) experienced high burnout, based on demographics, it showed that respondents were female, respondents were younger. (17-25 years), S1 education level, non-civil servant status, and teaching at SMP/Tsanawiyyah/equivalent levels show a high level of burnout. Abstrak. Sejak terjadinya pandemi covid-19 proses pembelajaran dilakukan dengan sistem pembelajaran jarak jauh. Menurut beberapa hasil survey pada guru yang mengajar dengan sistem pembelajaran jarak jauh menunjukan terjadinnya gejala-gejala burnout pada guru yang melakukan pembelajaran jarak jauh. Burnout merupakan sebuah sindrom kelelahan secara emosi, depersonalisasi, dan turun nya rasa pencapaian prestasi dan pribadi. Penelitian ini bertujuan mendapatkan gambaran burnout pada guru yang melaksankan pembelajaran jarak jauh di Kota Bandung, pengukuran dilakukan dengan menggunakan alat ukur MBI-ES (Maslach Burnou Inventory-Education Survey) yang telah diadaprtasi oleh Aulia Hanifah (2019) Sampel: 266 Guru yang melakukan PJJ di Kota Bandung. Berdasarakan hasil penelitian menunjukan bahwa 82% subjek mengalami burnout yang tinggi, dengan aspek tertinggi adalah low personal accomplishment, penelitian ini menunjukan bahwa sejumlah 216 reponden (82%) mengalami burnout yang tinggi, berdasarkan demografi menunjukan bahwa responden berjenis kelamin wanita, responden berusia lebih muda (17-25 tahun), jenjang pendidikan S1, status kepegawayan non PNS, dan mengajar di tempat SMP/Tsanawiyyah/sederajat mnunjukang tingkat burnout yang tinggi.